2019
DOI: 10.1021/acs.jpca.8b12440
|View full text |Cite
|
Sign up to set email alerts
|

A Multireference Ab Initio Study of the Diradical Isomers of Pyrazine

Abstract: Three diradical pyrazine isomers were characterized using highly correlated, multireference methods. The lowest lying singlet and triplet state geometries of 2,3didehydropyrazine (ortho), 2,5-didehydropyrazine (para), and 2,6-didehydropyrazine (meta) were determined. Two active reference spaces were utilized. The complete active space (CAS) (8,8) includes the σ and σ* orbitals on the dehydrocarbon atoms as well as the valence π and π* orbitals. The CAS (12,10) reference space includes two additional orbitals c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
57
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(73 citation statements)
references
References 49 publications
12
57
4
Order By: Relevance
“…Singlet−triplet gaps of diradical isomers of pyrazine follow a trend different from benzynes, the para isomer exhibiting a significant gap (on the order of 1 eV), while splitting of the ortho and meta isomers is rather small. 79 Calculations based on USLG involve four correlated geminals, in a vein similar to para-benzyne, nitrogen π orbitals replacing carbon π orbitals at the substituted positions. Results of the computations are collected in Table 6.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
“…Singlet−triplet gaps of diradical isomers of pyrazine follow a trend different from benzynes, the para isomer exhibiting a significant gap (on the order of 1 eV), while splitting of the ortho and meta isomers is rather small. 79 Calculations based on USLG involve four correlated geminals, in a vein similar to para-benzyne, nitrogen π orbitals replacing carbon π orbitals at the substituted positions. Results of the computations are collected in Table 6.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 99%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%
“…At this point, it is worth mentioning that the diradical isomers of benzene need MR-based calculations to accurately describe the optimized geometrical parameters as well as energy separations between multiplets. 5−9 Very recently, the structures and other properties of spectroscopic interest of pyrazine isomers have been clarified by Scott et al 10 second-order complete active space second-order perturbation theory [CASPT2], 12 and multiconfigurational pair density functional theory [MC-PDFT] 13,14 ) with larger complete active spaces, CAS (such as CAS (8,8) and CAS (12,10)).…”
Section: Introductionmentioning
confidence: 99%
“…The calculated structures and properties of these diradical isomers show a strong dependence on the level of theory and dimension of CAS used. Scott et al 10 showed that the extended CAS is needed for the proper physical description of these diradical isomers. They used a CAS (12,10) to explore the nature of interaction of the unpaired electrons on the radical center with the nitrogen lone pair orbitals.…”
Section: Introductionmentioning
confidence: 99%